ANALISIS CASH FLOW DAN KINERJA KEUANGAN DENGAN MENGGUNAKAN DUPONT SYSTEM DI TOKO SEPATU NEW RESTU IBU - Patrisius Seran; Darwin Yopie Kefi; Melda Mariana Poeh; Noldy D. P. Mumu (P3M- Politeknik Negeri Kupang, 2020)
This study aims to determine cash flow and financial performance at the New Restu Ibu shoe store in Atambua, Belu, East Nusa Tenggara. The method used in this research is descriptive and quantitative. The analysis technique used is the DuPont System or ROI. The results of the study show that store cash flow based on income statements in 2016, 2017, 2018 and 2019 experienced profits. The financial performance of the New Restu Ibu shoe store using the Du Pont system model for 2016-2019 shows a decline, but Return On Investment (ROI) is above inflation and interest rates.